The design of multimedia storytelling - Bibi, Sarah; Sari, Dian Shinta; Putra, Muhammad Iqbal Ripo (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2020)
In teaching English, the use of media is essential to underpin and facilitate the process. With the recent waves of Technology, some teachers also make an exercise of a digital platform to develop new Media. It is easier to attract students to follow the lesson and also increase their pursuit of learning. This research directed to how the design of digital storytelling to teach narrative for students. The researcher used Educational Research and Development cycle from Borg and Gall (2007) which adjusted into five steps, namely (1) research and information gathering, (2) planning, (3) preliminary product developing, (4) preliminary field testing, and (5) primary product revision. The result of the research shows that digital storytelling can be utilised as a medium to teach narrative. The purpose of the medium must be communicative and attractive for the students. Equally, for the students, they are interested in using digital storytelling medium to learn about narrative. Hence, digital storytelling is designed to occupy those needs and is expected to be useful to teach narrative.